1997
DOI: 10.1002/art.1780400425
|View full text |Cite
|
Sign up to set email alerts
|

Azathioprine in Behçet's syndrome. Effects on long‐term prognosis

Abstract: Objective. To assess the effect of azathioprine (MA) treatment on long-term prognosis in Behget's syndrome.Methods. Patients (all male) who took part in a double-blind, placebo-controlled trial of AZA a mean f SD of 94 f 10 months previously were reevaluated.Results. The emergence of blindness (log rank 2 = 5.6, P = 0.02) and a 2-line drop in the visual acuity of the right eye (log rank 2 = 5.9, P = 0.015) occurred significantly more frequently among the patients originally allocated to the placebo group compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
8

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(76 citation statements)
references
References 9 publications
3
65
0
8
Order By: Relevance
“…Only 1 (11%) of 9 patients with posterior eye involvement had loss of useful vision in at least 1 eye at the end of the followup, whereas almost all patients had improvement of visual acuity once treatment was started. The improved prognosis may be attributed to the early aggressive treatment with immunosuppressive agents and oral corticosteroids (7,53) and possibly to the long-term use of cyclosporin in most patients (50,52). In agreement with Kural-Seyahi et al (7), we demonstrated that the frequency and severity of eye involvement decreased over time.…”
Section: Seventeen-year Study Of Behçet's Disease In Italysupporting
confidence: 90%
“…Only 1 (11%) of 9 patients with posterior eye involvement had loss of useful vision in at least 1 eye at the end of the followup, whereas almost all patients had improvement of visual acuity once treatment was started. The improved prognosis may be attributed to the early aggressive treatment with immunosuppressive agents and oral corticosteroids (7,53) and possibly to the long-term use of cyclosporin in most patients (50,52). In agreement with Kural-Seyahi et al (7), we demonstrated that the frequency and severity of eye involvement decreased over time.…”
Section: Seventeen-year Study Of Behçet's Disease In Italysupporting
confidence: 90%
“…25,26 Mycophenolate mofetil (MMF; 2-3 gm/day orally) is an inhibitor of T-and B-lymphocytes. Dapsone (2-3 mg/kg/day), through its anti-inflammatory and bactericidal properties, has a role in cutaneous disease.…”
Section: Managementmentioning
confidence: 99%
“…El tratamiento de la EB se hace de acuerdo con los síntomas y territorios comprometidos, principalmente se han utilizado corticoesteroides tópicos y sistémicos, inmunosupresores y fárma-cos biológicos anti factor de necrosis tumoral (FNT) alfa [12][13][14] . Para el compromiso de mucosas, especialmente en genitales con lesiones que, si son de mayor tamaño, pueden dejar cicatrices 15 , se recomienda iniciar terapia con agentes como lidocaína combinada con corticoesteroides tópicos.…”
Section: Discussionunclassified